2019
DOI: 10.3390/s19071659
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning Model for Subject-Independent Human Emotion Recognition Using Electrodermal Activity Sensors

Abstract: One of the main objectives of Active and Assisted Living (AAL) environments is to ensure that elderly and/or disabled people perform/live well in their immediate environments; this can be monitored by among others the recognition of emotions based on non-highly intrusive sensors such as Electrodermal Activity (EDA) sensors. However, designing a learning system or building a machine-learning model to recognize human emotions while training the system on a specific group of persons and testing the system on a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…ResNet and many other deep convolutional neural networks are brought up in the image domain with two-dimensional convolution operation for image feature extraction. If applying the original 2D ResNet, the 1D input signal should be rearranged to a 2D matrix, like in [11]. However, the 2D convolutional kernel will disturb the sequential distribution to extract features.…”
Section: Resnetmentioning
confidence: 99%
See 2 more Smart Citations
“…ResNet and many other deep convolutional neural networks are brought up in the image domain with two-dimensional convolution operation for image feature extraction. If applying the original 2D ResNet, the 1D input signal should be rearranged to a 2D matrix, like in [11]. However, the 2D convolutional kernel will disturb the sequential distribution to extract features.…”
Section: Resnetmentioning
confidence: 99%
“…Extensive comparisons also reveal that our three deep neural networks with EDA data outperform previous models with handcraft features on emotion recognition, which proves the great potential of the end-to-end DNN method.Information 2020, 11, 212 2 of 16 different subjects. Until now, researchers still haven't achieved a satisfying recognition accuracy [8][9][10][11]. Circumventing this problem, we make great attempts on subject-independent emotion recognition in this work.Many studies in the past years have focused on physiological signals, such as EEG [12,13], ECG [14,15], and EDA [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, sweating is controlled by the sympathetic nervous system (i.e., part of the autonomic nervous system), and changes in the skin conductance are indications of physiological or psychological arousal (e.g., fight-or-flight response) [48]. Research demonstrated that this kind of arousal is significantly related to brain functions that regulate motor, sensory, and cognitive skills [44,49,50]. For example, when emotionally agitated (e.g., on the eve of an exam), sweat production is increased, resulting in an increase in the EDA as well (e.g., higher cognitive load).…”
Section: Electrodermal Activitymentioning
confidence: 99%
“…The system described in [15] uses the time differences between consecutive R-waves of QRS complexes, also called RR intervals, for mental stress identification in firefighters. In several works, a comparison between ML and DL methods for stress recognition has been carried out, also showing that Convolutional Neural Networks (CNNs) can outperform ML conventional methods [16,17].…”
Section: Introductionmentioning
confidence: 99%